Motion sickness, stress and the endocannabinoid system - Choukèr, Alexander; Kaufmann, Ines; Kreth, Simone; Hauer, Daniela; Feuerecker, Matthias; Thieme, Detlef; Vogeser, Michael; Thiel, Manfred; Schelling, Gustav (PLOS ONE, 2010)
BACKGROUND: A substantial number of individuals are at risk for the development of motion sickness induced nausea and vomiting (N&V) during road, air or sea travel. Motion sickness can be extremely stressful but the neurobiologic mechanisms leading to motion sickness are not clear. The endocannabinoid system (ECS) represents an important neuromodulator of stress and N&V. Inhibitory effects of the ECS on N&V are mediated by endocannabinoid-receptor activation. - METHODOLOGY/PRINCIPAL FINDINGS: We studied the activity of the ECS in human volunteers (n = 21) during parabolic flight maneuvers (PFs). During PFs, microgravity conditions (<10(-2) g) are generated for approximately 22 s which results in a profound kinetic stimulus. Blood endocannabinoids (anandamide and 2-arachidonoylglycerol, 2-AG) were measured from blood samples taken in-flight before start of the parabolic maneuvers, after 10, 20, and 30 parabolas, in-flight after termination of PFs and 24 h later. Volunteers who developed acute motion sickness (n = 7) showed significantly higher stress scores but lower endocannabinoid levels during PFs. After 20 parabolas, blood anandamide levels had dropped significantly in volunteers with motion sickness (from 0.39+/-0.40 to 0.22+/-0.25 ng/ml) but increased in participants without the condition (from 0.43+/-0.23 to 0.60+/-0.38 ng/ml) resulting in significantly higher anandamide levels in participants without motion sickness (p = 0.02). 2-AG levels in individuals with motion sickness were low and almost unchanged throughout the experiment but showed a robust increase in participants without motion sickness. Cannabinoid-receptor 1 (CB1) but not cannabinoid-receptor 2 (CB2) mRNA expression in leucocytes 4 h after the experiment was significantly lower in volunteers with motion sickness than in participants without N&V. - CONCLUSIONS/SIGNIFICANCE: These findings demonstrate that stress and motion sickness in humans are associated with impaired endocannabinoid activity. Enhancing ECS signaling may represent an alternative therapeutic strategy for motion sickness in individuals who do not respond to currently available treatments.